Anticonvulsant mechanism of saponins fraction from adventitious roots of Ficus religiosa: possible modulation of GABAergic, calcium and sodium channel functions - Singh,Damanpreet (2016)
ABSTRACT In our previous studies, quantified saponins-rich fraction from adventitious root extract of Ficus religiosa L., Moraceae, showed anticonvulsant effect in acute, as well as chronic mice models of epilepsy. The present study was designed to reveal putative anticonvulsant mechanism of quantified saponins-rich fraction using target specific animal models. The anticonvulsant effect of quantified saponins-rich fraction was initially studied in maximal electroshock and pentylenetetrazol test at 1, 2 and 4 mg/kg; i.p. doses. Based on the results of initial anticonvulsant testing, different groups of mice were injected with vehicle or quantified saponins-rich fraction (4 mg/kg; i.p.), 30 min prior to an injection of N-methyl-D-aspartic acid (100 mg/kg; s.c.), bicuculline (5 mg/kg; i.p.), strychnine hydrochloride (2 mg/kg; i.p.), BAY k-8644 (37.5 µg; i.c.v.), veratridine (500 µg/kg; i.p.) and the convulsive episodes were studied. Treatment with the extract (1, 2 and 4 mg/kg) showed significant protection in maximal electroshock and pentylenetetrazol-induced convulsion tests, in a dose-dependent manner. Moreover, quantified saponins-rich fraction at 4 mg/kg dose showed significant increase in latency to clonic convulsions, decrease in seizure severity and increase in average wave amplitude in bicuculline, BAY k-8644 and veratridine tests, respectively, as compared to vehicle control. However, SRF treatment failed to abolish N-methyl-D-aspartic acid and strychnine-induced convulsions, indicated by insignificant change in the appearance of turning behavior and onset of tonic extension, respectively, as compared to vehicle control. From the results of present study, it is concluded that quantified saponins-rich fraction suppress maximal electroshock, pentylenetetrazol, bicuculline, BAY k-8644 and veratridine-induced convulsions, indicating its GABAergic, Na+ and Ca2+ channel modulatory effects. Further it can be correlated that quantified saponins-rich fraction causes deactivation of voltage-gated Na+ and Ca2+ channels, without effecting ligand-gated Na+ and Ca2+ channels. More studies are required at molecular levels using in vitro techniques to understand the exact molecular interactions of quantified saponins-rich fraction with these pathways.